Hamer met tekst: "Aan G.W. Melchers van Neh. de Lieme" (1903?), aan andere zijde: "Van Melchers aan de Centrale" (1947?)
Hamer met tekst: "Aan G.W. Melchers van Neh. de Lieme" (1903?), aan andere zijde: "Van Melchers aan de Centrale" (1947?).